Windows, Elphinstone building - Ghosh, Ayan (2023)
The Elphinstone Building is built in the Venetian Gothic style, popular in Mumbai during the late nineteenth century. The style originated in Venice, which was a great maritime and financial power in the Middle Ages, with influences from Byzantine and Islamic architecture. Its maritime origin is reflected in the mooring rope motif used in the decking balustrades.